MAJAS PERBANDINGAN DALAM NOVEL HAFALAN SHALAT DELISA KARYA TERE LIYE - Khairunnisak, Fitri; Sinaga, Mangatur; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is to describe the form of comparison in Tere Liye's Hafalan Shalat Delisa novel and describe the meaning of the comparative form in Tere Liye's novel Hafalan Shalat Delisa. This study used descriptive qualitative method. Data obtained using reading techniques and note taking techniques. Then, the data is analyzed by reading the written text first then recording the parts according to the problems to be studied using a small book. From the data obtained in the novel Hafalan Shalat Delisa by Tere Liye, comparative forms of comparison are found in the form of parables which have characteristics such as: like, like, like and like. A figure of speech that has characteristics such as: door leaf, beach lip, blue lips, green eyes, calm face, enclosing the city, breaking down the walls of the heart, calm face, green eyes lit, golden hearts, grilling meaning. Pengasanan that has characteristics: moving, swaying, vibrating, swallowed, wrapping, grilling, white-winged bicycle, softening, preying, clumping, landing gracefully, waving, soft, licking, melting, being hit. The meaning of the comparison form consists of the meaning of differences in character figures, the meaning of equations, figurative meanings and the meaning of comparison.Key Words: Figure of Speech Comparison, Hafalan Shalat Delisa, Tere Liye